Cosmological constraints from H ii starburst galaxy apparent magnitude and other cosmological measurements. Issue 3 (27th July 2020) - Cao, Shulei; Ryan, Joseph; Ratra, Bharat
ABSTRACT: We use H ii starburst galaxy apparent magnitude measurements to constrain cosmological parameters in six cosmological models. A joint analysis of H ii galaxy, quasar angular size, baryon acoustic oscillations peak length scale, and Hubble parameter measurements result in relatively model-independent and restrictive estimates of the current values of the non-relativistic matter density parameter Ω _m_0 and the Hubble constant H 0 . These estimates favour a 2.0–3.4σ (depending on cosmological model) lower H 0 than what is measured from the local expansion rate. The combined data are consistent with dark energy being a cosmological constant and with flat spatial hypersurfaces, but do not strongly rule out mild dark energy dynamics or slightly non-flat spatial geometries.